Socio-Ecological Framework in the Implementation of the Environmental Conscious Early Childhood Education CSR Program by AFT Pattimura - Tiara Cherani; Ken Bima Prawira Atmaja; Samuel F. Syaranamual; Sara Marlis Youwe (Journal of Social Research, 2024)
This Research aims to assess the implementation of the Socio-Ecological Framework within the Corporate Social Responsibility (CSR) program initiated by PAUD Sadar Lingkungan, under the auspices of AFT Pattimura. The research primarily focuses on evaluating the program's effectiveness in enhancing environmental awareness and waste management skills among early childhood learners and the local community in Negeri Laha, Ambon. A qualitative research methodology, utilizing a case study approach, was employed. Data were collected through comprehensive interviews with participants, educators, and stakeholders, supplemented by direct observations of program activities. The results reveal that the application of the Socio-Ecological Framework significantly improves waste management understanding and skills among children and enhances environmental consciousness within the community. Moreover, the program has demonstrably contributed to community empowerment through practical training and environmentally oriented activities. These findings underscore the potential of integrating the Socio-Ecological Framework into CSR programs to achieve substantial positive impacts on environmental education outcomes and social sustainability at the local level. The study advocates for the continued expansion and refinement of CSR initiatives to broaden their reach and efficacy in environmental education. This research provides valuable insights for the development and enhancement of CSR programs in the field of environmental education.